Teaching English for Young Learners Using Vocabulary Cards - Sriwulandari, Novi; Yaqin, Muhammad Ainul; Dewi, Risma Kartika; Ihsan, Mas Darul; Trisnantasari, Ika; Ndaung, Ernita (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
Introducing English to children aged 0-12 years as a foreign language is very important considering that they are in the "Golden Period", a time when their brains quickly absorb the language they have acquired. This is useful for preparing them to face global competition considering that English is an international language. Community service in Segoromadu village, Gresik district aims to teach vocabulary (names of animals found in the surrounding environment) using the learning media "Vocabulary Cards" to 10 children aged 6-8 years in Segoromadu. Activity methods include demonstrations and assistance to children for 6-8 year. In this activity, they were taught various kinds of vocabulary about animals and fruit in the surrounding environment through games using the learning media "Vocabulary Cards". The results of this community service activity show that the students were very enthusiastic about participating in the learning process, they felt happy and their vocabulary about animals and fruit in the surrounding environment increased.